Dependence of reactive species generation on microwave pulse parameters in atmospheric argon/oxygen plasma. (3rd September 2018) - Jeong, S Y; Nam, W J; Lee, J K; Yun, G S
Abstract: The generation of reactive species in argon/oxygen plasma driven by a pulsed microwave has been investigated using global simulation. The applied power was given for varying pulse periods and duties with a constant average power. The differences in the trends for species densities with regard to the pulse parameters are analyzed based on the timescales of individual species. The density of electrons in the pulse case is not linearly dependent on the instantaneous power density, which is explained by identifying the dominant loss and source of electrons. In a simulation with the continuous power as a reference, the densities of most of the reactive species increase with the power, as expected. A more realistic global simulation has also been developed by taking the time-varying plasma length into account, as observed in real experiments using a resonator type power source. The simulation shows that the use of pulsed power can increase the average power coupling efficiency by minimizing the duration of the impedance mismatch.